Induced polyploidization in Brassica campestris L. (Brassicaceae) - Kumar, G.; Dwivedi, K. (Цитология и генетика, 2014)
Present experimental design has been made up to obtain crop with higher ploidy level via synthetic polyploidization. Since ploidy manipulation is generally associated with the obtainment of some increased enviable traits of the crop and also provides them greater adaptability to unfavorable or harsh circumstances as compared to its diploids counterparts. Thus, herein present research autotetraploids of Brassica campestris L. have been lucratively achieved by the application of colchicine. Two methods of treatment were utilized i.e. seed treatment and seedling treatment. No polyploidy could be obtained through seed treatment while seedling treatment responded well towards polyploidy. However, the status of autotetraploidy has been confirmed by cytomorphological investigations of treated plants as against its diploids counterparts. For the purpose, morphological parameters such as increased stomata size, pollen diameter, flower size, reproductive organs whereas reduction in plant height, leaf length, leaf breadth, stomata frequency, number of flowers/inflorescence etc. were appraised. Further, cytological observations were made that had clearly revealed the doubling of genome in the autotetraploids as compared to diploids. Meanwhile, pollen fertility and size of pollen grains were evaluated as well.